THE IMPORTANCE OF CYBERSECURITY AWARENESS FOR CHILDREN - Yuliana Yuliana (Faculty of Law Universitas Lampung, 2022)
Online school during the COVID-19 pandemic makes the children prone to cyberattacks and malware. Therefore, cybersecurity awareness among children is critical. Online games and stories caused children to neglect their studying time. Therefore, this paper aims to describe the importance of cybersecurity awareness among children. Analyses were performed by using a literature review. Inclusion criteria are review and research articles. Inclusion criteria are review and research articles that were read twice to reduce the bias, then were summarized and narrated descriptively. Results revealed that cybersecurity awareness could be increased by digital literacy training. Children should be taught how to avoid risky behavior online. The cybersecurity awareness program is suitable for children to avoid phishing, pornography, cyberbullying, identity theft, and breaking of privacy. Children must be taught how to keep their passwords safe and private. They also need to be more cautious when playing online games. In conclusion, digital literacy and cybersecurity programs can be taught to children. These programs are suitable for raising cybersecurity among children.